Analisis Perubahan Sikap Uni Eropa Terhadap Impor Minyak Kelapa Sawit Indonesia - Pradhana, Muhammad Aditya; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
The European Union is one of the largest energy user in the world, but due to lack of natural resources the European Union fullfill energy needs by import. To reduce its energy imports the European Union created the Renewable Energy Directive to stimulate the use and production of alternative energy such as biofuels. Biofuel is an alternative energy made from vegetable oils. One of the vegetable oils used by the European Union in making biofuels is palm oil. in 2017 the European Union made a resolution to stop imports of palm oil from Indonesia in 2021 due to environmental issues. Palm oil plantations in Indonesia are considered not sustainable and violate human rights. In 2018, the European Union raised the Renewable Energy Directive II, which delayed the ban on imports of palm oil from 2021 to 2030. The purpose of this study was to find out the reasons behind the change of attitude by the European Union in the import of palm oil. In analyzing the change, this study uses the theory of new institutionalism that sees at the interests that exist within the European Union and European Union member states to achieve even greater goals